Can’t Disconnect Even After-Hours: How Work Connectivity Behavior After-Hours Affects Employees’ Thriving at Work and Family - Yang, Yang; Yan, Rui; Meng, Yan (Frontiers in Psychology, 2022)
As more organizations adopt telecommuting or working from home, the work-connected behavior of their employees during non-working hours increases, weakening the boundary between work and family. However, no study has clearly identified whether and how work connectivity behavior after-hours (WCBA) affects employees’ work and family status. Therefore, using role theory, we explored the mechanisms by which WCBA affects employees’ thriving at work and family through work–family enrichment and work–family conflict, and compared the impact of different levels of support for family members on work–family enrichment and conflict, using the Johnson–Neyman method. Our analysis of two-wave data from 257 employees led to the following findings. (1) WCBA had a positive impact on thriving at work, but not on family. (2) There is a ‘double-edged sword’ effect on the impact of WCBA on thriving at work, meaning that work–family enrichment can positively influence thriving at work and negatively influence work–family conflict. (3) There is a double-edged sword effect on the impact of WCBA on thriving at family, meaning that work–family enrichment can positively influence thriving at family and negatively influence work–family conflict. (4) The support of family members moderates the double-edged sword effect between WCBA and thriving at work, in that it can strengthen the positive effects of work–family enrichment (below 3.32 points or above 4.19 points) and weaken the negative effects of work–family conflicts (below 4.28 points). (5) Support from family members reinforces the positive impact of work–family enrichment (above 3.46 points) on thriving at family. Thus our study reveals the mechanisms by which WCBA affects the thriving at work and family of employees, and identifies potential methods for managing different levels of work–family enrichment and work–family conflict from the perspective of family member support.